Three interesting wood rotting macro-fungi from Jharkhand, India - Manoj Emanuel Hembrom; Arvind Parihar; Kanad Das (Journal of Threatened Taxa, 2016)
Routine surveys of mycologically unexplored forest areas of Jharkhand, followed by a thorough examination of macro-fungal collections reveal two hitherto unrecorded poroid species (Basidiomycete) for Indian mycobiota namely, Ganoderma elegantum and Perenniporia bambusicola, and a less known hydnoid wood-rotting species Beenakia fuliginosa.  Detailed taxonomic descriptions coupled with illustrations are provided for all three taxa and compared with allied taxa.